Profiling the DNA-binding specificities of engineered Cys2His2 zinc finger domains using a rapid cell-based method - Meng, Xiangdong (Oxford University Press, 2007)
The C(2)H(2) zinc finger is the most commonly utilized framework for engineering DNA-binding domains with novel specificities. Many different selection strategies have been developed to identify individual fingers that possess a particular DNA-binding specificity from a randomized library. In these experiments, each finger is selected in the context of a constant finger framework that ensures the identification of clones with a desired specificity by properly positioning the randomized finger on the DNA template. Following a successful selection, multiple zinc-finger clones are typically recovered that share similarities in the sequences of their DNA-recognition helices. In principle, each of the clones isolated from a selection is a candidate for assembly into a larger multi-finger protein, but to date a high-throughput method for identifying the most specific candidates for incorporation into a final multi-finger protein has not been available. Here we describe the development of a specificity profiling system that facilitates rapid and inexpensive characterization of engineered zinc-finger modules. Moreover, we demonstrate that specificity data collected using this system can be employed to rationally design zinc fingers with improved DNA-binding specificities.